2014
DOI: 10.3988/jcn.2014.10.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Association between Ischemic Stroke and Vascular Shear Stress in the Carotid Artery

Abstract: Background and PurposeVascular shear stress is essential for maintaining the morphology and function of endothelial cells. We hypothesized that shear stress in the internal carotid artery (ICA) may differ between patients with ischemic stroke and healthy control subjects.MethodsICA shear stress was calculated in 143 controls and 122 patients with ischemic stroke who had a normal ICA or an ICA with <50% stenosis. The stroke group included patients who presented with a first-ever or recurrent ischemic stroke but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…For a proper measurement of carotid stenosis or occlusion, duplex ultrasonography was performed with electrocardiogram triggering and a high-frequency 5-12 MHz (12L5) linear transducer (Terason t3000, Teratech Corporation, Burlington, MA, USA) by a certified neurosonographer, as reported previously [15]. The ultrasonographic examination was done within 1 week after stroke events or at the same day with TOF-MRA during the health checkup.…”
Section: Three-dimensional Tof-mra Examinations and Carotid Ultrasonographymentioning
confidence: 99%
“…For a proper measurement of carotid stenosis or occlusion, duplex ultrasonography was performed with electrocardiogram triggering and a high-frequency 5-12 MHz (12L5) linear transducer (Terason t3000, Teratech Corporation, Burlington, MA, USA) by a certified neurosonographer, as reported previously [15]. The ultrasonographic examination was done within 1 week after stroke events or at the same day with TOF-MRA during the health checkup.…”
Section: Three-dimensional Tof-mra Examinations and Carotid Ultrasonographymentioning
confidence: 99%
“…The alteration of the carotid ESS plays a significant role not only in atheromatous plaque formation and progression but also in its vulnerabilization, a process that modifies the composition of the plaque towards a more unstable phenotype, increasing the risk of distal embolization and thus being directly linked with the risk of stroke. In a clinical study on 22 stroke patients and 143 controls, Jeong et al demonstrated that carotid ESS is significantly lower in patients who experienced ischemic stroke as compared to controls, indicating a possible causal relationship between carotid ESS and ischemic brain injury [145].…”
Section: Carotid Endothelial Shear Stress and Ischemic Strokementioning
confidence: 99%
“…A recent study on 100 patients undergoing endarterectomy found that the alteration of carotid ESS is directly associated with embolic signals during carotid exposure in endarterectomy, demonstrating the role of ESS in atheromatous plaque embolism, a main cause of ischemic stroke [147]. Moreover, the relationship between low ESS and ischemic stroke has been clearly evidenced by the study of Jeong et al, who found that carotid ESS is significantly lower in patients with lacunar infarction as compared to controls [145]. At the same time, a recent study published by Pedigri et al on ApoE −/− mice, demonstrated a direct link between the magnitude and direction of shear stress and the composition of atherosclerotic plaques in the carotid arteries.…”
Section: Carotid Endothelial Shear Stress and Ischemic Strokementioning
confidence: 99%
“…Shear stress helps create an endothelial transport barrier between blood and underlying tissues while promoting BBB integrity in the brain 96, 97. The internal carotid artery, which branches out from the common carotid artery, is a major blood‐supplying vessel to the brain and serves as a low‐resistance pathway for CBF autoregulation 98. Patients with DM exhibit accelerated atherosclerosis and increased susceptibility to arterial thrombosis, which have been attributed to increased shear stress–induced platelet activation, adhesion, and aggregation on the subendothelium 99.…”
Section: Mechanisms Of Ischemia/reperfusion Damage In Diabetic Strokementioning
confidence: 99%